Pengaruh Religiusitas Dan Konformitas Teman Sebaya Terhadap Etika Sopan Santun Siswa Madrasah Aliyah Tri Bhakti - Ibnu Mahmudi; Silvia Yula Wardani (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2022)
This study aims to determine the effect of religiosity and peer conformity on the etiquette of courtesy of Madrasah Aliyah Tri Bhakti Pagotan students in 2021. The research design is an expost facto study. Data collection techniques using a questionnaire. There are 3 questionnaires developed in this study, namely the religiosity questionnaire, peer conformity and ethical manners. The sampling technique used was random sampling. The data analysis technique used multiple linear regression. The results of the study showed the effect of religiosity on etiquette of the students of Madrasah Aliyah Tri Bhakti Pagotan. of 9.596 Meanwhile, the influence of peer conformity on the etiquette of courtesy of Madrasah Aliyah Tri Bhakti Pagotan students. by 19.14%.